On Asymptotic Classification of Solutions to Fourth-Order Differential Equations with Singular Power Nonlinearity - Astashova, Irina (Mathematical Modelling and Analysis, 2016)
The asymptotic behavior of all solutions to the fourth-order Emden– Fowler type differential equation with singular nonlinearity is investigated. The equation is transformed into a system on the three-dimensional sphere. By investigation of the asymptotic behavior of all possible trajectories of this system an asymptotic classification of all solutions to the equation is obtained.